gDefrag: Graph-Based Landscape De-Fragmentation - Mestre, Frederico (2019)
This package provides a set of tools to help the ecological de-fragmentation of landscapes divided by linear transportation infrastructures. It works by prioritizing the different sections of these infrastructures (e.g. roads, railways) to increase the available amount of a given resource for widlife.